2009
DOI: 10.1111/j.1755-5949.2008.00076.x
|View full text |Cite
|
Sign up to set email alerts
|

Open‐Label Support for Duloxetine for the Treatment of Panic Disorder

Abstract: Panic disorder with or without agoraphobia is a common, often chronic and refractory anxiety disorder. Although a number of pharmacotherapies are now indicated for panic disorder, many patients do not respond to available interventions. We hypothesized that duloxetine, a serotonin-norepinephrine reuptake inhibitor (SNRI) that has greater initial noradrenergic effects than venlafaxine, would have broad efficacy for individuals with panic disorder. Fifteen individuals with panic disorder with or without agorapho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 13 publications
0
23
0
2
Order By: Relevance
“…The opportunity to have another therapeutic option with fewer adverse effects is important and helpful. Other researchers, such as Simon et al, have hypothesized and confirmed that duloxetine, a serotonin-norepinephrine reuptake inhibitor with greater initial noradrenergic effects than venlafaxine, has broad efficacy in individuals with panic disorder 9,10. Our interest in duloxetine lies in the possibility of treatment for panic disorder with the added benefit of resolution of gastric symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…The opportunity to have another therapeutic option with fewer adverse effects is important and helpful. Other researchers, such as Simon et al, have hypothesized and confirmed that duloxetine, a serotonin-norepinephrine reuptake inhibitor with greater initial noradrenergic effects than venlafaxine, has broad efficacy in individuals with panic disorder 9,10. Our interest in duloxetine lies in the possibility of treatment for panic disorder with the added benefit of resolution of gastric symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…It has been used as a treatment outcome measure for panic disorder as well as a variety of other disorders, such as bipolar disorder, major depression, and body dysmorphic disorder Phillips & Rasmussen, 2004;Rodriguez, Bruce, Pagano, & Keller, 2005;Simon, Kaufman, et al, 2009). …”
Section: Range Of Impaired Functioning Tool (Life-rift)mentioning
confidence: 99%
“…Although an open-label study showed promise for the efficacy of the SNRI duloxetine (Simon, Kaufman, et al, 2009), controlled data are needed. SNRIs are generally well-tolerated and have safety and side-effect profiles similar to those of SSRIs.…”
Section: Antidepressantsmentioning
confidence: 99%
“…The side effects experienced by at least 10% but ! 25% of the subjects reported in the study by Simon et al [41] included: constipation, dry mouth, nausea, headache, sexual dysfunction, urinary hesitation, insomnia and sedation. Only 2 patients discontinued the trial because of side effects.…”
Section: Duloxetinementioning
confidence: 99%
“…A single study [41] on 15 subjects suggested that duloxetine could reduce symptoms' severity, with 8 patients not experiencing full panic attacks in the past 2 weeks and 4 achieving full remission.…”
Section: Duloxetinementioning
confidence: 99%